Optimizing and Controlling of Dissolved Oxygen in Advanced HA-A/A-MCO Sludge Reduction Process - Zuo, Ning; Ji, Fang-Ying (Asian Journal of Chemistry, 2012)
In order to explore the method of improving phosphorous and nitrogen removal in sludge reduction technologies, an advanced process combining excess sludge reduction and phosphorous and nitrogen removal is developed, for short, HA-A/A-MCO process (hydrolysis-acidogenosis-anaerobic/anoxic-multistep continuous oxic tank), which realizes phosphorous removal through hydrolysis acidification of raw sewage and phosphorus-release sludge improving phosphorus-release level and through eliminating anaerobic phosphorous accumulating sewage. Through controlling lower dissolved oxygen concentration (0.5-1.5 mg/ L) and adopting orthogonal test, we research preferable dissolved oxygen controlling concentration of each oxic tank (No. 1 oxic tank, No. 2 oxic tank and No. 3 oxic tank). Results show that preferable dissolved oxygen controlling concentration of No. 1 oxic tank, No. 2 oxic tank and No. 3 oxic tank is 0.8, 1.0 and 1.0 mg/L, respectively. Under the condition of optimal operating mode, the removal rate of COD, total notrogen and total phosphorus in HA-A/A-MCO system is up to 97.8, 78.9 and 99.3 %, respectively. Moreover, in the condition of lower dissolved oxygen concentration, HA-A/A-MCO process can obtain excellent effect of pollutant removal and sludge reduction simultaneously, which resolves the contradict that sludge reduction leads to oxygen demand increasing of wastewater treatment system so as to increase energy consumption of aeration.